Pengaruh Kompensasi Work Life Balance, dan Lingkungan Kerja terhadap Turnover Intention PT. Bina Pratama Sakato Jaya Kab. Solok-Selatan - Lara Yurma Putri; Afriyeni Afriyeni (ARZUSIN, 2026)
Studies on employee turnover intention have been widely conducted, but discussions that specifically link compensation, work-life balance, and the work environment in the context of production/factory employees remain limited. This study aims to analyze the effect of compensation, work-life balance, and the work environment on the turnover intention of employees at PT Bina Pratama Sakato Jaya, South Solok Regency. This study employed a quantitative approach with a survey design, involving 50 respondents selected through the total sampling technique. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression using SPSS. The results show that compensation has a positive and significant effect on turnover intention, whereas work-life balance and the work environment have negative and significant effects on turnover intention. Simultaneously, the three variables have a significant effect on employee turnover intention. These findings strengthen the study of human resource management, particularly regarding the factors that influence employees’ intention to leave a company. The conclusion of the study emphasizes the importance of properly managing compensation, work-life balance, and the work environment as a strategy to reduce turnover intention among production employees.